Nursing systematization in a patient with Diabetes mellitus (Research, Society and Development, 2022)
Experience report of the case study type with an elderly patient, from the city of Muaná-PA, diagnosed with a chronic degenerative disease such as diabetes. Diabetes mellitus is a disease caused by the increase in blood glucose, which is the main source of energy for our body, in this way, the vast majority of the food we eat is transformed into glucose in the digestive system. With the objective of this theme, relate the knowledge of anatomy, histology, physiology, pathology, immunology and pharmacology. Apply the Systematization of Nursing Care in patients with diabetes. The objective of the article is to apply the Systematization of Nursing Care to patients with diabetes. Identify the affected NHB through the elaboration of the assistance plan. The present work is a descriptive study and was carried out through collection at the Centro de Especialidades Médicas (CEMEC) in Belém, with study and collections carried out on April 23, 2019. The elaboration of the case study allowed the identification of diagnoses regarding the affected basic human needs (NHB) in the patient, so that the nursing team can develop a care and intervention plan based on the clinical condition. It is concluded that, in view of this study, the nursing team has a relevance in the care of the patient with diabetes, and with the elaboration of the nursing care plan, it was shown to satisfactorily meet the aggravations of the case, ensuring rehabilitation and allowing better referrals to the situation.